2003
DOI: 10.1016/s0029-7844(02)03072-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum corticotropin-releasing hormone at midgestation in hispanic and white women

Abstract: These data demonstrate that ethnicity is a significant factor affecting corticotropin-releasing hormone concentrations at midgestation in the Hispanic and white populations. The use of ethnicity-specific medians to estimate the ethnicity-specific MoM for the corticotropin-releasing hormone concentrations may enhance the predictive value of midgestational maternal corticotropin-releasing hormone as a screening parameter for the prediction of preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Other studies have reported higher CRH in whites than Hispanics (32) and three studies have reported higher CRH levels in whites than Blacks (10, 18, 41). One study also reported lower levels of pregnancy CRH in Hispanics than Blacks (41).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies have reported higher CRH in whites than Hispanics (32) and three studies have reported higher CRH levels in whites than Blacks (10, 18, 41). One study also reported lower levels of pregnancy CRH in Hispanics than Blacks (41).…”
Section: Discussionmentioning
confidence: 91%
“…The samples were cooled, centrifuged and stored at −70 C degrees. Briefly, either 150 ul (for <33 weeks since last menstrual period, LMP) or 40 ul (for ≥33 weeks since LMP) was extracted with a final concentration of 87.5% methanol and was assayed using previously described methods (10, 32). Assay sensitivity was 10.8 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…loss of appetite) may lead to growth restriction. As research suggests the possibility of differences in HPA axis function and the prevalence of health risk behaviors during pregnancy by race/ethnicity (Glynn et al 2007; Chen et al 2010; Siler Khodr et al 2003; Field et al 2002), it is important that further research considers these possible differences when examining potential mechanisms leading to disparities in adverse birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…During mid-gestation there is a rapid increase in the concentration of CRH in the maternal plasma (38). This occurs alongside production of surfactant in the fetal human lung beginning after week 24 of gestation, which corresponds to the saccular stage of lung development and the earliest consistently documented threshold of viability.…”
Section: Discussionmentioning
confidence: 99%